Using Technology-Based Media for Teaching Speaking in Intercultural Education - Titi Rokhayati; Ana Widiyanti (Bina Nusantara University, 2022)
The research aimed to study how did mobile-phone were used for teaching speaking in intercultural education? and was the use of mobile phone for teaching speaking in intercultural education effective? Intercultural competence could be seen in the teaching of speaking since the students had to reflect their ideas and opinions orally. Thus, the speaking ability would be much supported by intercultural education. To reach this, the use of technology-based media like mobile-phone in teaching speaking was needed to make it easier and more interesting. In the past decade, several studies have sought to determine the use of technology in education; however, in the university context, the issues of mobile phone used for teaching speaking in intercultural education had not been discussed extensively. The research employed explanatory sequential mix-method research. The instrument of the research was an observation, questionnaire, and test. The research population was 40 students of the fifth semester of the English Education Program of Purworejo Muhammadiyah University. The finding shows that mobile phone is used as the primary tool to access the material and learning platform. Using mobile phones, the student’s speaking ability is improved by 18,3%. In addition, the finding shows that the use of mobile phones for teaching speaking in intercultural education is effective to help the teacher in delivering the material and boosting the students’ motivation to speak.